2020
DOI: 10.1101/2020.05.14.20094821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission of aerosols through pristine and reprocessed N95 respirators

Abstract: During the Covid-19 pandemic, pristine and reprocessed N95 respirators are crucial equipment towards limiting nosocomial infections. The NIOSH test certifying the N95 rating, however, poorly simulates aerosols in healthcare settings, limiting our understanding of the exposure risk for healthcare workers wearing these masks, especially reprocessed ones. We used experimental conditions that simulated the sizes, densities and airflow properties of infectious aerosols in healthcare settings. We analyzed the penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Given the wide differences in test conditions, results are summarized by disinfection agent for N95s only, for agents with >5 samples or those agents identified in the disinfection efficacy section as achieving >3 log reduction of SARS-CoV-2, including ethanol, hydrogen peroxide, peracetic acid, PX-UV, UVGI, autoclaving, and heat. Autoclaving (n=14) 14,30,34,42,45,55,57,59 and ethanol disinfection (n=14) 15-17, 29, 42, 45, 53, led to failures within two disinfection cycles in 12 and 13 tests, respectively. This indicates these methods cannot be utilized for N95 reuse.…”
Section: Mask Reusementioning
confidence: 99%
See 1 more Smart Citation
“…Given the wide differences in test conditions, results are summarized by disinfection agent for N95s only, for agents with >5 samples or those agents identified in the disinfection efficacy section as achieving >3 log reduction of SARS-CoV-2, including ethanol, hydrogen peroxide, peracetic acid, PX-UV, UVGI, autoclaving, and heat. Autoclaving (n=14) 14,30,34,42,45,55,57,59 and ethanol disinfection (n=14) 15-17, 29, 42, 45, 53, led to failures within two disinfection cycles in 12 and 13 tests, respectively. This indicates these methods cannot be utilized for N95 reuse.…”
Section: Mask Reusementioning
confidence: 99%
“…Hydrogen peroxide disinfection (n=20) 15,19,27,29,30,36,45,51,57,[59][60][61]68 , dry heat (n=19) 12, 16, 19, 21, 29, 33-35, 42, 45, 49, 50, 52, 54 , UVGI (n=13) 15,16,29,35,42,45,46,52,[59][60][61][62] , and ethylene oxide (n=5) 19,[59][60][61] all had promising results.…”
Section: Mask Reusementioning
confidence: 99%
“…Other studies, some with limited numbers and varied fit tests, noted preserved fit after dry heat at 70°C × 30 minutes, 70°C × 60 minutes, 65 75°C × 30 minutes., and a dry rice cooker 149–164 °C × 3 minutes. 70 Chen et al 71 found well-preserved fit and filtration up to 3 cycles of both dry heat at 75°C × 60 minutes and 100°C × 30 minutes at 75%RH. Fischer et al 52 found some fit failures after the third 70°C heat cycle.…”
Section: Ffr Decontaminationmentioning
confidence: 99%
“… 53 , 78 Another recent report of the effects on 0.3 μm particle penetration of 7 FFR decontamination methods found very little change after 10 VHP cycles but damage after the third HPGP cycle, using 3 N95 models. 71 Pressure gradient data suggest that all methods damaged filter function by weakening the electret. 71 Filter damage following plasma and ionized methods may be related to higher HP concentrations.…”
Section: Ffr Decontaminationmentioning
confidence: 99%
See 1 more Smart Citation